Evaluación de los riesgos mecánicos en el área de producción y su incidencia en accidentes laborales en la empresa Lincoln. - Nuñez Veloz, Sebastián Eduardo (2025)
The present research project was developed at Lincoln Company in the oven production line. After observing the occurrence of workplace accidents within the company, a risk identification process was carried out, revealing that the primary risk factor is mechanical. This means that a significant portion of the accidents is related to machines, tools, and equipment within the oven production area. Following the preliminary identification, a mechanical risk assessment was conducted using the William Fine method, which classifies risks based on their occurrence, exposure, and impact on the operator. This assessment allowed for the development of a series of procedures, instructions, and additional documentation that, when compiled, form a proposed safety manual for the oven production line at Lincoln Company. Additionally, this research calculates the company's occupational incidence rate, which was determined based on data collected through surveys conducted with company operators.